Pastoral Kehadiran: Wujud Pengembalaan Umat Dalam Gereja Sinodalitas - Kristeno, Marianus Rago; X, Intansakti Pius (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The church is a living community of believers gathered by Christ into a "flock". Shepherding people in the Church has an important meaning as part of the pastoral tradition from the time of Jesus to the present. The task of shepherding comes from the mandate of Jesus himself as the Good Shepherd. Shepherding is considered important in meeting the spiritual and material needs of the people as well as maintaining togetherness and brotherhood in the Church community. Writing this article uses a descriptive qualitative approach using the library study method which is carried out by collecting various writings, both in print media, theses, articles, journals, papers, etc. that are relevant to the material discussed in this article. Furthermore, the shepherding of the people is manifested in pastoral presence, where the presence of the shepherd in the midst of the people becomes a symbol of Christ's presence and provides attention, care and love to the people. The synodal church which was revived by Pope Francis was highlighted as a movement to create a community that walks together towards salvation, with the active participation of all people and the important role of pastoral officers as representatives of Christ who guide and accompany the people. In conclusion, shepherding and pastoral presence play a vital role in guiding, maintaining and strengthening the faith and brotherhood of people in the Church community who walk together towards the salvation promised by the Father.